2020
DOI: 10.3389/fpsyg.2020.01035
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Turnover Intention Among People With Disabilities Working in Special Employment Centers: The Moderation Effect of Organizational Commitment

Abstract: With the goal of contributing to the growth of research on people with disabilities in employment, in particular in relation to their job satisfaction (JS), organizational commitment (OC), and turnover intention (TI), this study explores the effect of JS on TI among employees with disabilities and the moderation effect of OC and its four dimensions on this main relationship. A total of 245 Special Employment Center (SEC) employees in Spain answered a questionnaire. To analyze the results, a descriptive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
0
27
0
2
Order By: Relevance
“…This seems to be inconsistent with the previous research results. Previous studies have shown that, compared with low affective commitment, the relationship between variables (e.g., job resource and engagement, satisfaction with co-workers and supervisors and turnover intention) was stronger under the high affective commitment ( Dominguez et al, 2020 ; Romeo et al, 2020 ). This may be related to the complex role of high affective commitment in the relationship among variables.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This seems to be inconsistent with the previous research results. Previous studies have shown that, compared with low affective commitment, the relationship between variables (e.g., job resource and engagement, satisfaction with co-workers and supervisors and turnover intention) was stronger under the high affective commitment ( Dominguez et al, 2020 ; Romeo et al, 2020 ). This may be related to the complex role of high affective commitment in the relationship among variables.…”
Section: Discussionmentioning
confidence: 94%
“…This is somewhat similar to the results of previous studies. For example, previous studies indicated that affective commitment can moderate the relationship between job resources and engagement ( Dominguez et al, 2020 ), and the relationship between satisfaction with coworkers and supervisors, and lower turnover intention ( Romeo et al, 2020 ). It can be seen that the higher the level of affective commitment, there is more work engagement and less turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the years, there have been intense studies dedicated to job satisfaction (Hussain and Xian, 2019), in the field of social and behavioral sciences (Berberoglu, 2018), and in the field of education (Ahn and Chaoyu, 2019), Such studies referred to job satisfaction as the level to which an individual is inclined towards a certain job (Yousaf et al, 2018) and the overall feeling of an individual to the different job aspects (Karimi and Rahimi, 2020). More importantly, there are several thousands of studies dedicated to the job satisfaction topic (Tett and Meyer, 1993) to the extent that more studies have been done on the topic compared to any other variable (Romeo et al, 2020). Such studies focused on examining the antecedent factors of job satisfaction, job satisfaction dimensions, and the relationship between job satisfaction, job performance, and job turnover as job satisfaction can be connected to any job aspect and it plays a key role in the effectiveness of the organization (Van der Heijden et al, 2018).…”
Section: Literature Review and Related Theoriesmentioning
confidence: 99%
“…Maaitah et al (2018) reported that lower job burnout and turnover intention may be attributed to higher job satisfaction levels. Romeo et al (2020) on the other hand, examined individual perceptions among knowledge workers and found their satisfaction levels to adversely influence their turnover intention.…”
Section: Introductionmentioning
confidence: 99%
“…The results of some studies reported that job satisfaction is negatively associated with turnover among nurses [ 16 18 ]. Low job satisfaction is the most common cause of nurses’ turnover and intention to leave [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%